Analysis of the changes in communication and social interactions during the transformation of a traditional team into an agile team. Issue 9 (23rd March 2018) - Espinosa‐Curiel, Ismael Edrein; Rodríguez‐Jacobo, Josefina; Vázquez‐Alfaro, Erika; Fernández‐Zepeda, José Alberto; Fajardo‐Delgado, Daniel
Abstract: Traditional software teams that implement agile methodologies frequently experience difficulty working efficiently as agile teams. While agile methodologies support and promote social activities and behaviors, the understanding of the social phenomena and challenges that arise during the transformation of traditional teams into agile teams is limited. We conducted an extensive 10‐month case study in a software enterprise to analyze the changes in the communication and social interactions of employees during the transformation process, and to delineate the social challenges that arise during this process. Using social interaction registers, we collected data on the communication and social interactions of employees, first when they worked as a traditional team and then as an agile team. Then, we processed the data using social network analysis methods to identify the differences between these 2 types of teams and to create graphs of communication and social interaction networks. We identified that the transformation process influences formal, informal, oral, and written communication and increases conjunctive and disjunctive social interactions. Further, from the results of interviews conducted with all the enterprise members, we identified 5 social challenges to transforming a traditional team into an agile one. The results of this research suggest that the transformation process requires broad changes in the relationships and interactions among employees. Abstract :